2007
DOI: 10.1002/ab.20194
|View full text |Cite
|
Sign up to set email alerts
|

Executive cognitive functioning and the recognition of facial expressions of emotion in incarcerated violent offenders, non‐violent offenders, and controls

Abstract: Violence is a social problem that carries enormous costs; however, our understanding of its etiology is quite limited. A large body of research exists, which suggests a relationship between abnormalities of the frontal lobe and aggression; as a result, many researchers have implicated deficits in so-called "executive function" as an antecedent to aggressive behaviour. Another possibility is that violence may be related to problems interpreting facial expressions of emotion, a deficit associated with many forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
88
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 48 publications
10
88
2
3
Order By: Relevance
“…For example, two studies found specific relations of neurocognitive function with aggressive but not with nonaggressive conduct problems [Giancola et al, 1998;Hancock et al, 2010], whereas two other studies failed to find such a distinction [Baker and Ireland, 2007;Hoaken et al, 2007]. One potential explanation for this discrepancy is the aggregation of different types of nonaggressive conduct problems, which assumes that each type of nonaggressive misbehavior is equally linked to neurocognitive function.…”
Section: Introductionmentioning
confidence: 87%
“…For example, two studies found specific relations of neurocognitive function with aggressive but not with nonaggressive conduct problems [Giancola et al, 1998;Hancock et al, 2010], whereas two other studies failed to find such a distinction [Baker and Ireland, 2007;Hoaken et al, 2007]. One potential explanation for this discrepancy is the aggregation of different types of nonaggressive conduct problems, which assumes that each type of nonaggressive misbehavior is equally linked to neurocognitive function.…”
Section: Introductionmentioning
confidence: 87%
“…Conversely, aggressive responses seem to be suppressed in healthy individuals when recognizing fear in others 19 . Consistent with this explanation, Hoaken et al 18 found that non-clinical violent offenders were significantly worse in facial affect recognition compared to non-violent offenders and controls, and that emotion recognition correlated with executive functioning abilities including associative learning, strategy formulation as well as working memory 18 .…”
Section: Introductionmentioning
confidence: 97%
“…In any event, false interpretation of facial affect may lead to inappropriate social behavior, including impulsive aggression even in innocuous social situations 18 . Conversely, aggressive responses seem to be suppressed in healthy individuals when recognizing fear in others 19 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, inmates with high psychopathic traits appear to show more selective attention problems, compared to non-psychopathic inmates (Hiatt et al 2004;Pham et al 2003). Hoaken et al (2007) demonstrated that incarcerated violent offenders performed significantly more poorly at a cognitive empathy task, compared to non-violent offenders. Furthermore, Broomhall (2005) showed impaired complex prefrontal functioning in offenders with reactive aggression and largely intact functions in offenders with primarily instrumental aggression.…”
Section: Prefrontal Brain Functioningmentioning
confidence: 99%